(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This paper is concerned with the concept of weakly (τ_1,τ_2)-continuous functions. Furthermore, several characterizations and some properties of almost weakly (τ_1,τ_2)-continuous functions are investigated.